2021
DOI: 10.1016/j.ajem.2020.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular diseases burden in COVID-19: Systematic review and meta-analysis

Abstract: Background High rate of cardiovascular disease (CVD) have been reported among patients with novel coronavirus disease (COVID-19). Meanwhile there were controversies among different studies about CVD burden in COVID-19 patients. Hence, we aimed to study CVD burden among COVID-19 patients, using a systematic review and meta-analysis. Methods We have systematically searched databases including PubMed, Embase, Cochrane Library, Scopus, Web of Science as well as medRxiv pre-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
103
3
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(125 citation statements)
references
References 230 publications
(127 reference statements)
10
103
3
9
Order By: Relevance
“…However, there was no significant association between mortality in the patients with CVDs and COVID-19 ( Table 2). Hessami et al, in a metaanalysis including 159,698 COVID-19 patients reported a high burden of CVDs in patients with SARS-COV-2 infection, which was significantly associated with mortality and ICU admission [61]. Moreover, in the current meta-analysis, we found that the proportion of SARS-COV-2 infection in Iranian patients with hypertension was 21.1 %.…”
Section: Discussionsupporting
confidence: 55%
“…However, there was no significant association between mortality in the patients with CVDs and COVID-19 ( Table 2). Hessami et al, in a metaanalysis including 159,698 COVID-19 patients reported a high burden of CVDs in patients with SARS-COV-2 infection, which was significantly associated with mortality and ICU admission [61]. Moreover, in the current meta-analysis, we found that the proportion of SARS-COV-2 infection in Iranian patients with hypertension was 21.1 %.…”
Section: Discussionsupporting
confidence: 55%
“…Several studies identified that markers of inflammation and myocardial injury, like troponin T elevation, are associated with poor outcomes and overall increased mortality rates ( 9 , 11 , 12 , 14 , 16 , 18 ). Our data also showed that troponin elevation, particularly as levels continue to rise, is associated with increased mortality rates.…”
Section: Cases and Discussionmentioning
confidence: 99%
“…While there are guidelines on the diagnosis and management of respiratory failure, pneumonia, and sepsis-associated with SARS-CoV-2, there is a lack of guidance for the diagnosis and management of these associated cardiac complications despite the increased prevalence seen in this disease process. The paucity of high-quality best-practice evidence leaves clinicians with equipoise on how to best manage COVID-19 related cardiovascular complications, particularly in the critically ill ( 9 , 11 , 12 , 14 – 16 ). Here, we review our institutional data and describe recommendations detailing the management of acute cardiovascular complications in critically ill patients with COVID-19.…”
mentioning
confidence: 99%
“…During 2020, many meta-analyses and meta-meta-analyses reported the positive association between underlying diseases, especially CVD, and the illness severity among COVID-19 patients [216][217][218][219][220]. Resveratrol can alleviate the numerous factors associated with CVD, so it has potential as a functional supplement to reduce COVID-19 illness severity in patients displaying poor prognosis.…”
Section: Resveratrol and Cvd Related To Covid-19mentioning
confidence: 99%